Knowledge and confidence of junior medical doctors in discussing and documenting resuscitation plans: a cross‐sectional survey. Issue 12 (22nd December 2021) - Bryant, Jamie; Waller, Amy; Pickles, Rob; Hullick, Carolyn; Price, Emma; White, Ben; Willmott, Lindy; Bowman, Alison; Knight, Anne; Ryall, Mary‐Ann; Sanson‐Fisher, Rob
Abstract: Background: A resuscitation plan is a medically authorised order to use or withhold resuscitation interventions. Absence of appropriate resuscitation orders exposes patients to the risk of invasive medical interventions that may be of questionable benefit depending on individual circumstances. Aims: To describe among junior doctors: (i) self‐reported confidence discussing and completing resuscitation plans; (ii) knowledge of resuscitation policy including whether resuscitation plans are legally enforceable and key triggers for completion; and (iii) the factors associated with higher knowledge of triggers for completing resuscitation plans. Methods: A cross‐sectional survey was conducted at five hospitals. Junior doctors on clinical rotation were approached at scheduled training sessions, before or after ward rounds or at change of rotation orientation days and provided with a pen‐and‐paper survey. Results: A total of 118 junior doctors participated. Most felt confident discussing (79%; n = 92) and documenting (87%; n = 102) resuscitation plans with patients. However, only 45% ( n = 52) of doctors correctly identified that resuscitation plans are legally enforceable medical orders. On average, doctors correctly identified 6.8 (standard deviation = 1.8) out of 10 triggers for completing a resuscitation plan. Doctors aged >30 years were four times more likely to have high knowledge of triggers for completing resuscitation plans (odds ratio 4.28 (95% confidence interval 1.54–11.89); P = 0.0053). Conclusion: Most junior doctors feel confident discussing and documenting resuscitation plans. There is a need to improve knowledge about legal obligations to follow completed resuscitation plans, and about when resuscitation plans should be completed to ensure they are completed with patients who are most at risk.